2021
DOI: 10.3390/ijms22094792
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Resveratrol Intake on the Metabolic Health of the Offspring

Abstract: Maternal nutritional imbalances, in addition to maternal overweight and obesity, can result in long-term effects on the metabolic health of the offspring, increasing the risk of common non-communicable disorders such as obesity, diabetes and cardiovascular disease. This increased disease risk may also be transmitted across generations. Unfortunately, lifestyle interventions have shown reduced compliancy and limited efficacy. Resveratrol is a natural polyphenolic compound reported to have pleiotropic beneficial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Resveratrol is a polyphenolic compound produced naturally by plants and fruits, such as blackberries, blueberries, and the skin of red grapes, which has been shown to have anti-obesogenic, anti-inflammatory and antioxidant properties [ 10 , 11 , 12 ] and thus could potentially exert protective effects in the setting of maternal obesity. In rodent models, resveratrol has been used as a therapeutic agent to treat pregnancy disorders such as gestational diabetes [ 13 ], preeclampsia [ 14 ] and fetal growth restriction [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol is a polyphenolic compound produced naturally by plants and fruits, such as blackberries, blueberries, and the skin of red grapes, which has been shown to have anti-obesogenic, anti-inflammatory and antioxidant properties [ 10 , 11 , 12 ] and thus could potentially exert protective effects in the setting of maternal obesity. In rodent models, resveratrol has been used as a therapeutic agent to treat pregnancy disorders such as gestational diabetes [ 13 ], preeclampsia [ 14 ] and fetal growth restriction [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have indicated beneficial metabolic programming effects of maternal supplementation with polyphenols, including resveratrol, during the fetal and lactation stages, especially in the context of maternal HFD/obesity, as well as a reduction of body fat accumulation and metabolic disorders, such as hypertension, insulin resistance, and inflammation, and cognitive impairment, in the offspring in adulthood (reviewed in [96][97][98]). Since polyphenols have a wide range of activities, their beneficial effects are attributed to several interrelated mechanisms affecting oxidative stress, nutrient-sensing signals, and others [99].…”
Section: Resveratrol and Other Polyphenolsmentioning
confidence: 99%
“…Cook et al reported that lower hepatic fat deposition was associated with vegetable consumption, while consumption of dark green or yellow vegetables was associated with lower visceral fat and improved insulin sensitivity . Ingestion of garlic and onions may also reduce the risk of NAFLD . Tajima et al investigated 977 men and 1467 women aged 40–69 years and found no significant association between fruit and NAFLD in middle-aged men and women .…”
Section: Prevention Intervention and Treatment Strategies For Nafldmentioning
confidence: 99%
“…34 Ingestion of garlic and onions may also reduce the risk of NAFLD. 35 Tajima et al investigated 977 men and 1467 women aged 40−69 years and found no significant association between fruit and NAFLD in middle-aged men and women. 36 A study involving 91,436 subjects showed that increased coffee consumption was associated with a lower risk of NAFLD in Korean and daily consumption of over two cups of coffee reduced fat accumulation in the liver.…”
Section: Prevention Of Nafld Through Dietsmentioning
confidence: 99%